Peran Majelis Taklim Dalam Meningkatkan Pemahaman Keagamaan Jamaah Masjid - Junaidi Marbun; Ahmad Rivauzi (Prodi Pendidikan Keagamaan Islam, 2022)
The taklim assembly has an important role in fostering religious understanding of the pilgrims. This study aims to find out in depth how the role of the Baitul Makmur Taklim Assembly in improving the understanding of Islam, the method of this research method is qualitative with a case study approach. The object of study was the mothers of the Taklim Assembly at the Baitul Makmur Mosque of the West Freshwater Perumnas. Based on the results of the study, it was found that 1) The role of the Taklim Assembly in increasing the knowledge of jama'ah, namely a) Accommodating Jama'ah in studying Islam, b) Accommodate sakinah family education, c) Ba'da Ashar Routine Wirid. 2) The role of the Taklim Assembly in improving the Belief of Jama'ah, namely a) The Study of Tawhid Material, b) The Study of Afterlife Material. 3) The Role of the Taklim Assembly in Improving the Practice of Jama'ah, namely a) Asmaul Husna Training, b) Mukenah Washing, c) Implementation of the Body, d) Friday Mubarakah, e) Arisan, f) Yasinan.4) Supporting factors are a) Guidance from ustadz, b) Facilities and infrastructure, c) Willingness of mothers. 4) Inhibiting factors, namely a) Busyness of mothers, b) Physical Condition of the Body.